Development of Bisphosphonate-Conjugated Antibiotics to Overcome Pharmacodynamic Limitations of Local Therapy: Initial Results with Carbamate Linked Sitafloxacin and Tedizolid - Emmanuela Adjei-Sowah; Yue Peng; Jason Weeks; Jennifer H. Jonason; Karen L. de Mesy Bentley; Elysia Masters; Yugo Morita; Gowrishankar Muthukrishnan; Philip Cherian; X. Eric Hu; Charles E. McKenna; Frank H. Ebetino; et al. (MDPI AG, 2021)
The use of local antibiotics to treat bone infections has been questioned due to a lack of clinical efficacy and emerging information about Staphylococcus aureus colonization of the osteocyte-lacuno canalicular network (OLCN). Here we propose bisphosphonate-conjugated antibiotics (BCA) using a "target and release" approach to deliver antibiotics to bone infection sites. A fluorescent bisphosphonate probe was used to demonstrate bone surface labeling adjacent to bacteria in a S. aureus infected mouse tibiae model. Bisphosphonate and hydroxybisphosphonate conjugates of sitafloxacin and tedizolid (BCA) were synthesized using hydroxyphenyl and aminophenyl carbamate linkers, respectively. The conjugates were adequately stable in serum. Their cytolytic activity versus parent drug on MSSA and MRSA static biofilms grown on hydroxyapatite discs was established by scanning electron microscopy. Sitafloxacin O-phenyl carbamate BCA was effective in eradicating static biofilm: no colony formation units (CFU) were recovered following treatment with 800 mg/L of either the bisphosphonate or α-hydroxybisphosphonate conjugated drug (p < 0.001). In contrast, the less labile tedizolid N-phenyl carbamate linked BCA had limited efficacy against MSSA, and MRSA. CFU were recovered from all tedizolid BCA treatments. These results demonstrate the feasibility of BCA eradication of S. aureus biofilm on OLCN bone surfaces and support in vivo drug development of a sitafloxacin BCA.